Testing Tropiduchini Stål 1866 (Hemiptera: Tropiduchidae) monophyly, a young inter‐tropical taxon of mainly insular species: taxonomy, distribution patterns and phylogeny, with the description of a new genus from Papua New Guinea. (5th December 2016) - WANG, RONG‐RONG; LI, XIN‐YU; SZWEDO, JACEK; STROIŃSKI, ADAM; LIANG, AI‐PING; BOURGOIN, THIERRY
Abstract: A morphological phylogenetic analysis of the tribe Tropiduchini (Hemiptera: Tropiduchidae) is provided for 21 genera among the 26 recognized, including the new genus Oechalinella Wanggen.n., with a new species Oechalinella bifasciata Wangsp.n. Monophyly of the tribe is well supported by synapomorphies derived from the male genitalia. The strict consensus supports two subclades: (( Montrouzierana + Thymbra ) + Thaumantia + ) as sister to the clade ( Leptovanua + ( Vanua + Varma + ) + Daradacella + ). In the first subclade, the clade ( Montrouzierana + Thymbra ), distributed in New Caledonia and Papua New Guinea, is well supported by three synapomorphies based on the tegmina, while the Thaumantia + group is characterized by the conformation of the anal tube and male gonostyli, and distributed from Malesia to Papuasia and in Central Africa. The second subclade is largely distributed from China to Malesia, Papuasia, Southwestern and the Northwestern Pacific islands. The position of the genus Leptovanua remains uncertain. The Varma + clade is recovered in all analyses. Implied weighting analysis placed the Varma + lineage as sister to all other genera forming a new group ( Leptovanua + + (( Montrouzierana + Thymbra ) + Thaumantia + )). Fennah's definition of Tropiduchini is reviewed according to the phylogenetic results and an identification key to all genera is provided with a referenced synopsis of their distribution. Globally, Tropiduchini exhibits an inter‐tropical latitudinal distribution and a paradoxical bimodal longitudinal distribution pattern in continental Africa, South‐east Asia and the Pacific islands. Distribution data concern nearly 80% of insular taxa. The phylogenetical results suggest that: (i) the tribe originates from continental China; (ii) it evolved mainly from Papuasia by stepping‐stone colonization events, promoting subsequent insular speciation; and (iii) its evolution has mainly been directed by dispersion versus vicariance.